Geographic Barriers to Indexing: Examining Appalachia - Blevins, Emily W.; Woodward, Nakia J.; Loyd, Kelly; Castle, Aaron S.; Walden, Rachel R.; Wallace, Richard L. (Medical reference services quarterly, 2024)
The objective of this study was to examine the accuracy of indexing for "Appalachian Region"[Mesh]. Researchers performed a search in PubMed for articles published in 2019 using "Appalachian Region"[Mesh] or "Appalachia" or "Appalachian" in the title or abstract. Only 17.88% of the articles retrieved by the search were about Appalachia according to the ARC definition. Most articles retrieved appeared because they were indexed with state terms that were included as part of the mesh term. Database indexing and searching transparency is of growing importance as indexers rely increasingly on automated systems to catalog information and publications.